Malaysian Tualang Honey suppresses the angiogenic events in Endothelial cells induced by vascular endothelial growth factor - Abdul Khalid, Ahmad Firdaus; Ng, Chin Theng; Fong, Lai Yen; Tan, Jun Jie; Yakop, Fahmi; Kamaruddin, Nur Aqilah; Abdullah, Muhammad Nazrul Hakim; Yong, Yoke Keong (Universiti Kebangsaan Malaysia, 2022)
Anti-VEGF therapy has been used as the anti-angiogenic agent in cancer treatment. However, the treatment often couples with severe complications. Complementary natural products that offer similar anti-angiogenic potency with less side effects are sought as alternatives. Study showed that Malaysian Tualang Honey (MTH) can inhibit inflammation-induced vascular hyperpermeability in vitro and in vivo, but the effect on the angiogenesis process remains unclear. Thus, this study aims to determine the anti-angiogenic effects of MTH. Effects of MTH ranging from 0.3% to 0.9% on VEGF-induced human umbilical vein endothelial cells (HUVEC) angiogenesis was determined by proliferation, migration and tube-formation assays. Matrix metalloproteinase-2 (MMP-2) secretion from HUVEC and VEGF production from MCF7 cancer cells in response to MTH were also quantified by using ELISA kits. Suramin, an angio-suppressive agent was used as positive control. MTH significantly suppressed HUVEC proliferation (from 155% proliferation rate to 54%); migration (~ 50% inhibition rate) and tube-formation (69% reduction) induced by VEGF. These findings were explained by the significant reduction (p < 0.05) of VEGF-induced MMP-2 secretion in HUVEC with 39% suppression exhibited by 0.9% of MTH. MTH also significantly (p < 0.05) reduced VEGF secretion (19% reduction compared to control) in MCF7 breast cancer cells. Our findings suggest that the anti-angiogenic effects of MTH mainly targets endothelial cell through inhibition cell proliferation, migration and tube formation capacity, via suppression of MMP-2 secretion by the endothelial cells. However, MTH has less prominent effect on suppressing VEGF secretion by the MCF7 cancer cells.